Case report: A case of bradycardia triggered by diarrhea - Lei, Meixian; Cao, Yuan; Yuan, Mingqing; Xiong, Jie; He, Huabin (Frontiers in Medicine, 2024)
BRASH syndrome is a vicious cycle of hyperkalemia and bradycardia and is an under-recognized life-threatening clinical diagnosis. It is usually initiated by hypovolemia or hyperkalemia. We report here on the case of a 92-year-old man with hypertension and heart failure who presented to the emergency department with weakness following diarrhea. He was on amlodipine, benazepril, metoprolol, furosemide and spironolactone. The patient’s blood pressure was 88/53 mmHg and the serum creatinine was 241 μmol/L. Within 2 h, the patient’s heart rate decreased from 58 beats per minute to 26 beats per minute, and serum potassium levels gradually increased from 6.07 mmol/L to 7.3 mmol/L. The electrocardiogram showed a junctional escape rhythm with accidental sinus capture. The diagnosis of BRASH syndrome was made based on clinical symptoms, a biochemical profile and the results of an electrocardiogram. The patient was rapidly stabilized with the administration of intravenous calcium gluconate, dextrose and insulin, 5% sodium bicarbonate, 0.9% sodium chloride, furosemide, and oral zirconium cyclosilicate. Sinus rhythm at a heart rate of 75 bpm was detected 5 h later, along with normal serum potassium levels. After 2 weeks, kidney function returned to normal. Clinicians should be alert to patients with hyperkalemia and maintain a high index of suspicion for BRASH syndrome. Timely diagnosis and comprehensive intervention are critical for better outcomes in managing patients with BRASH.